A Comparative Study to Determine the Efficacy of Atosiban versus Nifedipine in Management of Preterm Labour - Vidya Gaikwad; Jay Patel; Suhas Gaikwad (Journal of Clinical and Diagnostic Research)
Introduction: Preterm Labour (PTL) remains a significant challenge in obstetrics, contributing to neonatal morbidity and mortality. The management of PTL involves the use of tocolytic agents to delay delivery, thereby allowing for further foetal development. Aim: To compare the tocolytic efficacy of Nifedipine and Atosiban in the management of PTL. Materials and Methods: This prospective interventional study was conducted at Dr. DY Patil Medical College, Hospital, and Research Centre, Pune, Maharashtra, India from October 2022 to August 2024. Ninety pregnant women between 24 to 34 weeks of gestation, diagnosed with PTL, were assigned to receive either Atosiban (n=45) or Nifedipine (n=45) according to the inclusion criteria. The primary outcomes measured were the duration of pregnancy prolongation, neonatal outcomes and Neonatal Intensive Care Unit (NICU) admissions. Chi-square tests or t-tests were used to compare these categorical variables. Results: Nifedipine was associated with a slightly higher percentage (36 cases, or 80%) achieving pregnancy prolongation for more than seven days compared to Atosiban (34 cases, or 75.56%). Nifedipine also demonstrated better neonatal outcomes and reduced NICU admissions (Nifedipine: 14 cases, or 31.11% vs. Atosiban: 20 cases, or 44.44%). However, Nifedipine was linked to a higher incidence of maternal side-effects , such as headache, hypotension and tachycardia, whereas Atosiban was better tolerated, with fewer reported side-effects . Atosiban was more frequently used in cases with earlier gestational ages, reflecting its utility in more acute clinical scenarios. Conclusion: Both Atosiban and Nifedipine were effective in managing PTL, with each drug offering distinct advantages depending on the clinical scenario. Nifedipine was more effective in prolonging pregnancy and improving neonatal outcomes, while Atosiban was associated with fewer maternal side-effects and is preferred in acute cases.